Recovering metal(loids) and rare earth elements from closed landfill sites without excavation: leachate recirculation opportunities and challenges - Lee, Hyeyeon; Coulon, Frederic; Beriro, D. J.; Wagland, Stuart T. (Elsevier, 2021)
Metal (loids) and Rare Earth Elements (REE) (‘metals’) are used in a wide range of products, and therefore, the improvement of expectations for everyday comforts with demand continues to grow. Metal-bearing wastes are a secondary source of raw material that can meet this demand by providing a previously unconsidered low impact supply source. Total annual leachate production is 1,056,716 m3. Therefore, landfill leachate emerges as a significant potential resource as it contains high concentrations of metals. However, realising a profitable return on investment for leachate processing is a challenge due to relatively low recovery rates of approximately 0.02% of total heavy metals in a landfill being leached out in 30 years. Variation within the multi-element value and the effect of other chemicals in these complex mixtures. There is a need to better understand the mechanisms and potential applicability of extraction methods for optimising metals recovery from leachate. This paper addresses this need by providing a systematic review of the critical factors and environmental conditions that influence the behaviour of metals within the landfilled waste. The paper provides a synthesis of how the factors and conditions may affect leachate recirculation efficiency for recovery in the context of a range of opportunities and challenges facing circular economy practitioners. To approach feasibility metal recovery economically from landfill leachate without energy-intensive and environmentally destructive, future research actions need to be initiated in lab-based and later on semi-pilot to pilot studies, which the review can help achieve the challenges.
Keywords: Circular economy; Non-intrusive investigation; Organic compounds; Mobility; Metal recovery